An exploratory model of personal financial well-being among Malaysian youth:a gender perspective - Falahati, Leila; Paim, Laily; Sabri, Mohamad Fazli (Persatuan Ekonomi Pengguna dan Keluarga Malaysia (MACFEA), 2012)
Financial well-being and its impact on the quality of life have received considerable attention in recent decades. A large number of studies have attempted to identify the dimensions of financial well-being and the effect of other factors, such as financial management, financial attitude, past experiences among various groups in relation to the development of personal financial well-being. However, the majority of studies on personal financial well-being among adolescents reveal notable gender differences. Evidence indicated that men and women's perceptions differ and that they are not necessarily only influenced by economic factors, but also by social and psychological issues. To identify gender differences in financial well-being, this study focuses on the perceived financial well-being of Malaysian college students. This study was carried out under (IRPA) funding. Data were collected from students in public and private Malaysian universities. The multi stage stratified random sampling technique was used. A total of 11 universities were randomly selected for the study and 350 questionnaires were distributed to students through the student affairs section of the respective university. Data were collected using self-administered questionnaires. A multi-group analysis approach using AMOS was applied to assess the moderating effect of gender. The findings indicated that gender significantly moderates the effect of factors on predicting financial well-being among male and female students.